2019
DOI: 10.1021/acschemneuro.9b00287
|View full text |Cite
|
Sign up to set email alerts
|

Activation of G-Protein-Coupled Receptor 30 Protects Neurons against Excitotoxicity through Inhibiting Excessive Autophagy Induced by Glutamate

Abstract: Autophagy is a protecting intracellular pathway to transmit unnecessary or dysfunctional components to the lysosome for degeneration. Autophagic imbalance is connected with neurodegeneration. Neurodegenerative diseases including Parkinson's disease, Alzheimer's disease, and Huntington's disease are closely related to excitotoxicity and neuronal loss. Activation of G-protein-coupled receptor 30 (GPR30), an estrogen membrane receptor, protects neurons from excitotoxicity-induced cell death. However, whether auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Many studies have confirmed that autophagy plays an important role in cardiac function and metabolism [ 24 , 25 ], and G1 shows a protective effect by regulating autophagy intensity in the nervous system [ 29 , 30 ]. In order to verify whether the cardiac protection of the G1 treatment in our study was related to autophagy, we detected the expression of LC3 and P62, which are reported as markers of autophagy [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have confirmed that autophagy plays an important role in cardiac function and metabolism [ 24 , 25 ], and G1 shows a protective effect by regulating autophagy intensity in the nervous system [ 29 , 30 ]. In order to verify whether the cardiac protection of the G1 treatment in our study was related to autophagy, we detected the expression of LC3 and P62, which are reported as markers of autophagy [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…G1 treated female mice also exhibited increased energy expenditure, lower body fat content, and reduced fasting cholesterol, glucose, insulin, and inflammatory markers [ 16 ]. Yue et al demonstrated that GPR30 activation reduced glutamate-induced excessive autophagy in neurons and protected neurons against excitotoxicity [ 29 ]. Wang et al reported that activation of GPR30 by G1 played a neuroprotection role via the regulation of astrocyte autophagy and supported astrocytic GPR30 as a potential drug target against ischemic brain damage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, the role of GPER1 in protecting brain neurons from hypoxia and ischemia remains controversial. It has been suggested that GPER1-mediated neuroprotection relies on the inhibition of apoptosis and excessive autophagy via the modulation of the PI3K-Akt-mTOR signaling pathway [ 79 ]. Since the role of autophagy in hypoxia/ischemia-induced brain pathology is ambiguous, the involvement of GPER1 in neuroprotection or neurotoxicity may be a result of interference with the autophagy process that determines the stroke duration and damage area.…”
Section: Neuroprotection Mediated By Membrane Ersmentioning
confidence: 99%
“…It can be speculated that it is depend on the types of cells, physiological functions, and types of stress stimuli that determine which types of G-protein subunits can activate mTORC1. The activation of G protein-coupled receptor 30 (GPR30, an estrogen membrane receptor) mainly regulates the PI3K–AKT–mTOR signaling pathway to inhibit excessive autophagy induced by glutamate and protect neurons from excitotoxicity [ 195 ]. The lysosomal GPR137B can interact with Rag GTPases to regulate mTORC1 in the absence of amino acids; however, autophagy is abnormal and lysosomes are damaged when GPR137B is knocked out, indicating that GPR137B can control the location and activity of mTORC1 and maintain lysosome morphology [ 196 ].…”
Section: Gpcrs-mediated Autophagymentioning
confidence: 99%